MODELS AND METHODS FOR FORMING REGIONAL CORPORATE STRUCTURES - K. Gerasimov (Вестник университета)
The basic models, mechanisms and methods of integration of regional corporate structures have been presented. The foreign and Russian experience in the formation of corporate structures has been considered. The structure of the integration mechanism in the context of the interaction of the external and internal environment of the organization has been discussed, which makes it possible to manage integration in the process of forming the corporate structure and its further development on the basis of identifying dominant factors in order to achieve a balanced state of the system. It has been shown, that the influence of large corporations on the economy of the region is determined by number of features. Russian practice indicates, that corporations receive substantial benefits from the region’s economy, and for regions the presence of large corporations often does not contribute to the development of the economic space. Nevertheless, modern realities determine the need for the development of corporate structures at the regional level.